Distributional dynamics of a specialized subterranean community oppose the classical understanding of the preferred subterranean habitats. Issue 3 (2nd August 2019) - Kozel, Peter; Pipan, Tanja; Mammola, Stefano; Culver, David C.; Novak, Tone
Abstract: Troglobionts are organisms that are specialized for living in a subterranean environment. These organisms reside prevalently in the deepest zones of caves and in shallow subterranean habitats, and complete their entire life cycles therein. Because troglobionts in most caves depend on organic matter resources from the surface, we hypothesized that they would also select the sections of caves nearest the surface, as long as environmental conditions were favorable. Over 1 year, we analyzed, in monthly intervals, the annual distributional dynamics of a subterranean community consisting of 17 troglobiont species, in relation to multiple environmental factors. Cumulative standardized annual species richness and diversity clearly indicated the existence of two ecotones within the cave: between soil and shallow subterranean habitats, inhabited by soil and shallow troglobionts; and between the transition and inner cave zones, where the spatial niches of shallow and deep troglobionts overlap. The mean standardized annual species richness and diversity showed inverse relationships, but both contributed to a better insight into the dynamics of subterranean fauna. Regression analyses revealed that temperatures in the range 7–10°C, high moisture content of substrate, large cross section of the cave, and high pH of substrate were the most important ecological drivers governing the spatiotemporal dynamics of troglobionts. Overall, this study shows general trends in the annual distributional dynamics of troglobionts in shallow caves and reveals that the distribution patterns of troglobionts within subterranean habitats may be more complex than commonly assumed.